Developing an Antibody–Drug Conjugate Approach to Selective Inhibition of an Extracellular Protein. (7th February 2019) - Love, Elizabeth A.; Sattikar, Afrah; Cook, Hannah; Gillen, Kevin; Large, Jonathan M.; Patel, Seema; Matthews, David; Merritt, Andy
Abstract: Antibody–drug conjugates (ADCs) are a growing class of therapeutics that harness the specificity of antibodies and the cell‐killing potency of small‐molecule drugs. Beyond cytotoxics, there are few examples of the application of an ADC approach to difficult drug discovery targets. Here, we present the initial development of a non‐internalising ADC, with a view to selectively inhibiting an extracellular protein. Employing the wellinvestigated matrix metalloproteinase‐9 (MMP‐9) as our model, we adapted a broad‐spectrum, nonselective MMP inhibitor for conjugation and linked this to a MMP‐9‐targeting antibody. The resulting ADC fully inhibits MMP‐9, and ELISA results suggest antibody targeting can direct a nonselective inhibitor. Abstract : Seeking a selectivity solution : We have worked towards an extracellular version of the antibody–drug conjugate (ADC) modality by conjugating a nonselective protease inhibitor to a high‐affinity antibody targeting a single protease. Detailed studies demonstrated that antibody binding kinetics could overcome poor small‐molecule selectivity, thus enabling simultaneous and selective binding to the target.